Bioaccumulation and trophic transfer of potentially toxic elements in the pelagic thresher shark Alopias pelagicus in Baja California Sur, Mexico. (July 2020) - Lara, Ariagna; Galván-Magaña, Felipe; Elorriaga-Verplancken, Fernando; Marmolejo-Rodríguez, Ana Judith; Gonzalez-Armas, Rogelio; Arreola-Mendoza, Laura; Sujitha, S.B.; Jonathan, M.P.
Abstract: Pelagic thresher shark ( Alopias pelagicus ) is a circumglobal species with high ecological and economic importance. Concentrations of mercury, selenium and cadmium in the muscle and liver tissues of A. pelagicus captured from Baja California Sur, Mexico were determined for assessing the potential human hazard. Results revealed that the average concentrations of Hg (0.76 mg kg −1 ) and Cd (0.18 mg kg −1 ) in muscle tissues were below the maximum permissible limits for human consumption. Se in the muscles were relatively low (mean: 0.30 mg kg −1   −1 ) resulting in a molar excess of Hg over Se. Average levels of hepatic Cd were extremely higher than the maximum limit for consumption. Organotropism of Hg was muscle > liver, whereas Se and Cd presented an order of liver > muscle. Biomagnification Factor (BMF) emphasized the trophic transfer of elements. Selenium Health Benefit value was negative (−3.76) posing potential health risks demanding regular monitoring for health risks. Graphical abstract: Unlabelled Image Highlights: Muscular Hg > hepatic Hg liver, whereas inverse for Cd and Se Hg and Cd levels in the muscles less than the permissible limits for consumption Trophic accumulation of Hg, Se and Cd from the preys